Modification of the discharge of lateral geniculate neurons during visual learning - Gibbs, CM (J Neurosci, 1986)
Visually conditioned heart rate change in the pigeon has been developed as a vertebrate model system for cellular analysis of associative learning. Previous studies have characterized the behavior, largely delineated the neural circuitry mediating the conditioning, and estimated the central processing time for the conditioned response. Most recently, this system has been used to investigate neuronal activity during conditioning along the visual pathways that transmit the conditioned stimulus (CS) information. It was first shown that neither maintained nor CS-evoked discharge of retinal ganglion cells changes during conditioning. Subsequently, we found that the thalamic and telencephalic components of the ascending tectofugal pathway show associative modification. We report here studies of the thalamofugal pathway, the avian homolog of the mammalian geniculocortical system. Single-cell activity was recorded in the thalamic relay of this pathway, the dorsal lateral geniculate equivalent (LGNe). This provided an opportunity to evaluate the generality of the training-induced modification found along the tectofugal pathway, and to determine if such modification occurs as peripherally as retinorecipient neurons. The results show that almost all LGNe neurons (97%) respond phasically to the onset of whole-field illumination. Most (94%) also respond to the unconditioned stimulus (US), footshock, some with increased and others with decreased discharge. Of cells receiving convergent input, those responding with decreased discharge to the US showed associative change (52%). Neurons that did not respond to both the CS and US, or that responded to the US with increased discharge, did not show associative modification. These findings suggest that the visual pathways transmitting CS information are not merely input lines, but undergo training-induced modification; such modification can occur as peripherally as the retinorecipient neurons of these pathways; and CS- US convergence is necessary but not sufficient for associative modification, since modifiability is apparently contingent on specific US response properties.